Green construction service management for community well being solution: an educational service perspective - Mohd Azmi, Nurmasfalina; Belal, H. M. (2017)
The green construction as well as green building’s sustainability depends on the future generation’s knowledge and participation of the community, including with understanding the consequences of individual behavior.Green Construction industry aims to enhance win-win situations among societal, environmental, and economic values.These win-win situation measure into three parts, namely sustainable construction, building, and planning. However, there is a lacking that, how the mentioned three parts can work together in improving societal, environmental and economic values. Therefore, our hypothesis that, there is need to make a beneficial relationship between service providers and recipients. In this research, we develop a relationship system framework among st three parties which is construction industries, educational service provider, and end users considering as recipients in the view of academic service. The data are collected thorough interview method and explained it by descriptive analysis.This research can help with overcoming the environmental challenges and enable it to succeed in the educational service by ensuring well-being value through knowledge and resource co-creation.